Thermal and mechanical properties of a multifunctional composite square honeycomb sandwich structure. (15th July 2016) - Yu, Guo-Cai; Feng, Li-Jia; Wu, Lin-Zhi
Abstract: A multifunctional composite square honeycomb sandwich structure (MCHSS) is developed which provides both high thermal conductivity and adequate mechanical property for a thermal management system. The out-of-plane thermal conductivity of MCHSS is improved by a simple method of coating highly oriented graphite film (HOGF), and investigated both theoretically and experimentally. There are two most efficient methods to further enhance the out-of-plane thermal conductivity of MCHSS: one is to increase the HOGF volume content, and the other, to decrease the interface thermal resistance. The maximum improvement is up to approximately 26 times for the measured out-of-plane thermal conductivity as compared with the traditional composite sandwich structures. Results indicate that, except for high specific thermal conductivity for thermal management, MCHSS also possess adequate mechanical properties for structural applications. Thus, MCHSS can be considered as a promising candidate for multifunctional structure material in the high-end heat dissipation field. Graphical abstract: Highlights: Highly oriented graphite film vastly improves thermal conductivity of composite sandwich structures. A maximum improvement in out-of-plane thermal conductivity of MCHSS is up to approximately 26 times. Increasing HOGF volume content and decreasing interface resistance are most efficient for improving thermal conductivity. MCHSS possesses the adequate out-of-plane compressive and shear properties.